The Influence of Social Media Interaction and Brand Engagement on Brand Awareness, Brand Image, and Brand Loyalty of Modern Bakery - Amanda; Siti Nurlaela (International Journal of Economics (IJEC), 2025)
This study aims to analyze the influence of social media interaction and customer brand engagement on brand awareness, brand image, and brand loyalty in the modern bakery industry in Indonesia. With a quantitative approach, this study collected data from 141 respondents who were social media users who had interacted with modern bakery brands. Data processing used Structural Equation Modeling (SEM) with SmartPLS 4. The results showed that social media interaction had a significant effect on customer brand engagement. Furthermore, social media interaction also had a significant direct effect on brand awareness, brand image, and brand loyalty. Path analysis showed an indirect effect of social media interaction through customer brand engagement on the three dependent variables, indicating a partial mediation effect. This study emphasizes the importance of active interaction on social media as a primary strategy in building brand awareness, brand image, and brand loyalty in the modern bakery industry. These findings provide important implications for modern bakery industry players in optimizing their digital marketing strategies to increase consumer engagement and loyalty.